Pengaruh Penguasaan Keterampilan Mengajar dalam Upaya Meningkatkan Guru yang Inovatif - Yhesa Rooselia Listiana; Arfadila Arfadila; Erlinda Erlinda; Shela Silvia; Siti Humaeroh (Journal on Education, 2023)
This study aims to get an overview of the teaching skills that must be possessed by teachers. There are 8 teaching skills that must be possessed by teachers, which include: asking skills, providing reinforcement skills, varying skills, explaining skills, opening and closing skills, skills guiding small group discussions, class management skills, and small group and individual teaching skills. . The application of teaching skills is very necessary as an effort to support success in learning. This study uses descriptive qualitative research with the aim of being able to describe the effect of teaching skills with innovative teachers on learning. By mastering these teaching skills, it is hoped that later teachers will be more varied in providing learning in the classroom.